You can if you think you can [soundrecording] - Peale, Norman Vincent 1898- (New York Simon & Schuster, 1988)
Demonstrates Peale's philosophy and action on overcoming adversity and achieve life goals by solving problems through "imagining a solution" that's already in our mind and using the art of creative anticipation.
Keywords: Success -- Religious aspects -- Christianity; Personality development; Philosophy; Psychology